Redução de MIR-218 no soro como biomarcador de pior prognóstico em entes com câncer gástrico - MARTINS, Nina Nayara Ferreira (Universidade Federal do Pará, 2019)
Recently, liquid biopsy has emerged as a promising tool for the identification of potential diagnosis, prognosis and/or predictive biomarkers in blood of patients with many different diseases, including cancer. MicroRNAs are among that potential biomarkers, and when deregulated, could contribute to the development of various types of cancer, such as gastric cancer. The literature demonstrates an association of miR-218 expression as a potential tumor suppressor associated with gastric cancer progression. However, only one previous study in Asiatic population evaluated the expression of circulating miR-218 in the serum of patients vs control. Therefore, the aim of this study was to evaluate the expression of miR-218 in the serum of patients with gastric cancer and its correlation with clinical-pathological characteristics. Samples were collected from 302 patients and 120 healthy subjects for analysis of mirR-218 expression by Real-Time Quantitative Polymerase Chain Reaction. The results demonstrated decreased expression of miR-218 in the serum of patients with gastric cancer in association with health subjects. In addition, the reduction of miR-218 expression was significantly associated with tumor invasion, presence of lymph node metastases, Lauren’s diffuse type, advanced stages of cancer, indicating worse prognosis. Therefore, corroborating with findings from the literature, theses results suggest the potential use of miR-218 in serum as a prognostic biomarker in gastric cancer patients.